2014
DOI: 10.7575/aiac.ijels.v.2n.2p.80
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Captioned Movies on Listening Comprehension

Abstract: With the advent of technology, the implication of authentic multimedia-based teaching materials are using widely in language classrooms. Technology can be in service of teaching different skills such as listening, reading, speaking and writing. Among these skills listening comprehension is a skill in which the learners have problems to master. Regarding this issue, utilizing captions for the education purposes has been a good motivation for conducting some research on the effects of captions of listening skill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…As it was referred to in 4.1.1 and 4.1.2, subtitling was found to leave positive impacts on different skills and sub-skills of language like vocabulary (Beauprez 2014;Ina 2014;Raine 2012;Rostam shirazi, et al, 2015), listening comprehension (Ghasemboland & Naffisi, 2012;Janfaza, et al, 2014;Latifi, et al, 2012), and speaking (Rokni & Ataeei, 2014). Subtitling in its various forms turned out to be conducive to speaking fluency and accuracy.…”
Section: Discussing the Third Research Questionmentioning
confidence: 90%
“…As it was referred to in 4.1.1 and 4.1.2, subtitling was found to leave positive impacts on different skills and sub-skills of language like vocabulary (Beauprez 2014;Ina 2014;Raine 2012;Rostam shirazi, et al, 2015), listening comprehension (Ghasemboland & Naffisi, 2012;Janfaza, et al, 2014;Latifi, et al, 2012), and speaking (Rokni & Ataeei, 2014). Subtitling in its various forms turned out to be conducive to speaking fluency and accuracy.…”
Section: Discussing the Third Research Questionmentioning
confidence: 90%
“…There were studies on the effect of caption on vocabulary learning done by Shabani and Zanussi (2015), and Beauprez (2014), Ina (2014) and Raine (2012) and all have reported the positive effects of subtitling on L2 vocabulary acquisition of EFL/English as a Second Language (ESL) learner. The research was conducted on the effect of subtitling on listening comprehension by Mohajer and Pourgharib (2014) and Janfaza, Javidi and Soori (2014). Both of these studies demonstrated positive effect of caption on listening.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies revealed that learning the English language in an EFL classroom using English movies can become very useful. Due to the recent availability of authentic videos, a huge number of foreign language classrooms across the world are now using captioned movies (Janfaza et. Al., 2014).…”
Section: Introductionmentioning
confidence: 99%